Lista de artículos en orden cronólogico - Boletín Técnico (1987)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Agroalimentarias::Estación Experimental Agrícola Fabio Baudrit Moreno (EEAFBM)